Pengembangan Jaringan Internet Antardesa di Kecamatan Gebang dengan Konektifitas Radio Ubiquite M5 Wireless Broadband (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Gebang district is govemment under the auspices of the district. Gebang sub-district consists of 240 villages and 37 sub-districts, the capital of this sub-districtis located in the gebang sub-district. In the gebang sub-district, it handles the affairs of population data for inter-village civil records, BLT, and social assistance. Homever, the obstacle in gebang sub-district lies in the internet network where the internet connetion speed is still slow so that performance is hampered. To optimize internet network from sub-district to inter-village, then an internet connection is needed that can be used in all villages in the gebang sub district using an Access Point and Mikrotik Router Board.